UI/UX Design for the Klaten Boarding House Application in the Widya Dharma University Klaten Area using Figma - Lija Santia Mahulae (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2023)
Looking for boarding houses has become something that is often questioned by students, especially new students who come from outside the area around the University. The very limited availability of information can cause difficulties for the community when searching for boarding houses. The purpose of this study was to produce a UI/UX design prototype for the Klaten Boarding House application which will display relevant and accurate information about the location of the boarding house, information on boarding facilities, costs and can place an order for the boarding house. The area that will be used as a research location is a boarding house around Widya Dharma Klaten University. In designing the UI/UX design, the Klaten Kos application prototype was made as attractive as possible by using Figma editing software. Data collection techniques carried out by the author are interviews, observation, and literature study. With this system, it is hoped that it will make it easier to find boarding houses according to your wishes and help boarding owners to promote boarding houses online.